2007
DOI: 10.1262/jrd.18092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Daily Treatment with Thai Herb, Kaempferia parviflora, in Hershberger Assay Using Castrated Immature Rats

Abstract: Abstract. The aim of the present study was to investigate the testosterone-like effect of Kaempferia parviflora (KP). Castrated immature rats were randomized and divided into two groups (control and KP-treatment groups). The rats (n=7-8) were treated daily for 5 days by oral route with water in the control group and 1,000 mg/kg of KP in the treatment group. All rats were decapitated 24 h after their last dose and then blood samples were collected for assay of serum FSH, LH, testosterone, progesterone and corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Consistent with the GH effects, KP has a gastroprotective effect and inhibits gastric ulcer formation by increasing gastric mucus and reducing gastric ulcer size in rats [3]. Hence, this reinforces the suggestion that KP increases rat body weight by directly or indirectly acting as testosterone.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Consistent with the GH effects, KP has a gastroprotective effect and inhibits gastric ulcer formation by increasing gastric mucus and reducing gastric ulcer size in rats [3]. Hence, this reinforces the suggestion that KP increases rat body weight by directly or indirectly acting as testosterone.…”
Section: Discussionsupporting
confidence: 82%
“…Nowadays, this plant is considered a Thai national herb. Based on studies using gas chromatographic techniques, many kinds of flavonoid substances, including 7,7,3,5,3,5,7,5,7,7, have been found in KP roots [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that aphrodisiac plant enhances sexual behaviors via an increase in the testosterone (Cek et al, 2007a). Trisomboon, Watanabe, Wetchasit, & Taya, (2007) showed that, serum testosterone levels significantly increase in immature rats orally treated with dry Kaempferia parviflora powder (1 g kg -1 ) in water for 5 days. Also, it has been reported that T. terrestris enhance testosterone levels in human and animals (Cek et al, 2007a).…”
Section: Reproductive Performancementioning
confidence: 99%
“…8,9) The extract of the rhizomes of K. parviflora and its constituents were revealed to exhibit several pharmacological activities, such as antiplasmoidal, antifungal, 2) antiinflammatory, [10][11][12] α-glucosidase inhibitory, 13) and xanthine oxidase inhibitory 1) activities and cytotoxicity of several tumor cell lines 14,15) as well as effect of P-glycoprotein function 16) and modulation of multi-drug resistance in cancer cells.…”
mentioning
confidence: 99%